Sarawak State Library (SLL) / Nurul Hasanah Hussien - Hussien, Nurul Hasanah (University Technology MARA Sarawak, 2013)
Throughout the 5-week term of my practical training at SLL, I was exposed to various types of employee training and development programs used by SLL in order to improve their staff skills and performances. Besides, there are a few techniques that SLL use to evaluate their staff competencies level and the effectiveness of the trainings. In this chapter, I will try to explain the effectiveness of training evaluation towards training and development management and how SLL practiced training evaluation as their former training and development tool which is still being used up until today especially when it comes to evaluate on the effectiveness of a training and development programs to its staff. During my practical training, I was also involved in several things related to training evaluation in SLL such as analyzing training evaluation form of the staff and analyzing the staff assessment skills. Later on in this chapter I will explain the training management concept and the reflections of the concept in my experience during practical training.